Entrepreneurial Intention among Students of Islamic Junior High School: Niat Wirausaha di Kalangan Siswa Sekolah Menengah Pertama Islam - Wijanarko, Haryo Bagus; Widyastuti, Widyastuti (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Entrepreneurship is increasingly recognized as a crucial strategy to address unemployment and foster economic growth in developing countries, including Indonesia. Specific Background: Early cultivation of entrepreneurial intention among students is essential, particularly in Islamic educational settings where character and responsibility are emphasized. Knowledge Gap: However, there is limited empirical evidence describing the current level of entrepreneurial intention among Islamic junior high school students. Aim: This study aims to provide a descriptive overview of entrepreneurial intention in students of SMP Islam Sidoarjo. Results: Using a descriptive quantitative design with proportionate stratified random sampling (n = 148 of 243 students), data were collected through a validated Likert-scale instrument. Findings reveal that 69% of students demonstrated a moderate level of entrepreneurial intention, 13% were in the high category, and 18% in the low category, indicating a tendency among students to develop entrepreneurial awareness. Novelty: This study highlights the psychological dimensions of entrepreneurship within an Islamic school context, showing the readiness of students to embrace entrepreneurial values from an early age. Implications: The results suggest that educational programs integrating entrepreneurship in Islamic junior high schools can strengthen students’ future capacity to create opportunities and contribute to sustainable economic development. Highlights: Most students show moderate entrepreneurial intention (69%). Study emphasizes psychological perspective in Islamic school context. Findings support early entrepreneurship education for sustainability. Keywords: Entrepreneurial Intention, Islamic Junior High School, Students, Psychology, Education